Mechanistic insight into insect declines is crucial for effective conservation - Benoit Guénard; Taylor A Bogar; Roger H Lee; Chi Man Leong; Runxi Wang; Mark KL Wong (Current Opinion in Insect Science, 2026)

Acoustic evidence for topographic blocking on a steep submarine canyon wall - Astrid B. Leitner; Chad M. Waluk; Kim R. Reisenbichler; Rob E. Sherlock; Bruce H. Robison; Kelly J. Benoit‐Bird (Limnology and Oceanography, 2026)
Diel vertical migration (DVM) is the largest mass‐movement of animals on Earth, with profound ecological and biogeochemical consequences. DVM has mostly been studied in the open ocean; however, at steep slopes, pelagic animals including vertical migrators must contend with the seafloor, emphasizing the importance of understanding DVM in these prevalent, critical habitats. Here we used active acoustics in combination with video to conduct a detailed study of the interactions of vertical migrators with the steep wall of a submarine canyon during their sunrise descent. We found regular and frequent, high‐density sunrise aggregations of animals consistent with seafloor blocking of descending vertical migrators across all seasons. While topographic blocking was thought to be primarily caused by nighttime advection of migrators over shallows by prevailing currents, here the occurrence of this phenomenon was observed to be largely independent of oceanographic drivers including advection as measured by an ADCP, providing evidence that behavior plays an important role. Advection, season, upwelling, and other environmental factors were found to impact specific characteristics of sunrise aggregations but not likelihood of occurrence. Given its intensity and prevalence, topographic blocking likely creates high‐quality, predictable foraging opportunities for a large diversity of predators and influences the abundance and habitat use of predators in the area. The steep slopes of this canyon, as with any abrupt bathymetry, juxtapose the deep and the shallow, the benthic and the pelagic, and the offshore and nearshore. Thus, topographic blocking may be prevalent in other steep canyons and at steep bathymetry more generally.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Regimes of bedforms created by down-slope density currents - Octavio E. Sequeiros; Benoit Spinewine; Gary Parker; Carlos Pirmez; Enrica Viparelli; Juan J. Fedele; Marcelo H. García; Débora Koller; Michele Bolla Pittaluga; Miwa Yokokawa (Earth-Science Reviews, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Detection of antibodies against the African parasite Trypanosoma brucei using synthetic glycosylphosphatidylinositol oligosaccharide fragments - Maurice Michel; Benoit Stijlemans; Dana Michel; Monika Garg; Andreas Geissner; Peter H. Seeberger; Daniel Varón Silva (Glycoconjugate Journal, 2025)
Trypanosoma brucei ( T. brucei ) parasites cause two major infectious diseases in Africa: African trypanosomiasis in humans (HAT) and Nagana in animals. Despite the enormous economic and social impact, vaccines and reliable diagnostic measures are still lacking for these diseases. The main obstacle to developing accurate diagnostic methods and an active vaccine is the parasite’s ability for antigenic variation, impairment of B cell maturation, and loss of B cell memory which collectively prevent the development of a long-lasting, effective immune response. The antigenic variation is sustained by random gene switching, segmental gene conversion, and altered glycosylation states of solvent-exposed regions of the corresponding variant surface glycoproteins (VSGs). These glycoproteins use a glycosylphosphatidylinositol (GPI) anchor for attachment to the membrane. GPIs of T. brucei have specific branched structures that are further heterogeneously galactosylated. Here, we synthesized a glycan fragment library containing T. brucei GPIs’ most prominent structural features and performed an epitope mapping using mice and human sera of infected specimens using glycan microarrays. The studies indicate that in contrast to VSGs, T. brucei GPIs are recognized by infection-induced short-lived Immunoglobulin M (IgM) and long-lasting Immunoglobulin G (IgG), suggesting a specific immune response against GPI structures. These findings enable the development of diagnostic tests based on synthetic antigens for the reliable diagnosis of human African trypanosomiasis and Nagana.

Thermal tolerance of Aedes aegypti mosquito eggs is associated with urban adaptation and human interactions - Souvik Chakraborty; Emily Zigmond; Sher Shah; Diya Dayal; Massamba Sylla; Jewelna Akorli; Sampson Otoo; Noah H. Rose; Carolyn S. McBride; Peter A. Armbruster; Joshua B. Benoit (Journal of Thermal Biology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Heliophysics Great Observatories and international cooperation in Heliophysics: An orchestrated framework for scientific advancement and discovery - Larry Kepko; Rumi Nakamura; Yoshifumi Saito; Angelos Vourlidas; Matthew G.G.T. Taylor; Cristina H. Mandrini; Xóchitl Blanco-Cano; Dibyendu Chakrabarty; Ioannis A. Daglis; Clezio Marcos De Nardin; Anatoli Petrukovich; Minna Palmroth; et al. (Advances in Space Research, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Brain metabolite levels in remitted psychotic depression with consideration of effects of antipsychotic medication - Hideaki Tani; Iska Moxon-Emre; Natalie J. Forde; Nicholas H. Neufeld; Kathleen S. Bingham; Ellen M. Whyte; Barnett S. Meyers; George S. Alexopoulos; Matthew J. Hoptman; Anthony J. Rothschild; Hiroyuki Uchida; Alastair J. Flint; et al. (Brain Imaging and Behavior, 2023)
Background The neurobiology of psychotic depression is not well understood and can be confounded by antipsychotics. Magnetic resonance spectroscopy (MRS) is an ideal tool to measure brain metabolites non-invasively. We cross-sectionally assessed brain metabolites in patients with remitted psychotic depression and controls. We also longitudinally assessed the effects of olanzapine versus placebo on brain metabolites. Methods Following remission, patients with psychotic depression were randomized to continue sertraline + olanzapine ( n = 15) or switched to sertraline + placebo ( n = 18), at which point they completed an MRS scan. Patients completed a second scan either 36 weeks later, relapse, or discontinuation. Where water-scaled metabolite levels were obtained and a Point-RESolved Spectroscopy sequence was utilized, choline, myo-inositol, glutamate + glutamine (Glx), N -acetylaspartate, and creatine were measured in the left dorsolateral prefrontal cortex (L-DLPFC) and dorsal anterior cingulate cortex (dACC). An ANCOVA was used to compare metabolites between patients ( n = 40) and controls ( n = 46). A linear mixed-model was used to compare olanzapine versus placebo groups. Results Cross-sectionally, patients (compared to controls) had higher myo-inositol (standardized mean difference [SMD] = 0.84; 95%CI = 0.25–1.44; p = 0.005) in the dACC but not different Glx, choline, N -acetylaspartate, and creatine. Longitudinally, patients randomized to placebo (compared to olanzapine) showed a significantly greater change with a reduction of creatine (SMD = 1.51; 95%CI = 0.71–2.31; p = 0.0002) in the dACC but not glutamate + glutamine, choline, myo-inositol, and N -acetylaspartate. Conclusions Patients with remitted psychotic depression have higher myo-inositol than controls. Olanzapine may maintain creatine levels. Future studies are needed to further disentangle the mechanisms of action of olanzapine.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Trace elements, dioxins and PCBs in different fish species and marine regions: Importance of the taxon and regional features - Aourell Mauffret; Tiphaine Chouvelon; Nathalie Wessel; Pierre Cresson; Daniela Bănaru; Jérôme Baudrier; Paco Bustamante; Rachida Chekri; Petru Jitaru; François Le Loc'h; Benoit Mialet; Vincent Vaccher; et al. (Environmental Research, 2023)

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

Genome of elegance coral Catalaphyllia jardinei (Euphylliidae) - Yifei Yu; Wenyan Nong; Wai Lok So; Yichun Xie; Ho Yin Yip; Jasmine Haimovitz; Thomas Swale; David M. Baker; William G. Bendena; Ting Fung Chan; Apple P. Y. Chui; Kwok Fai Lau; et al. (Frontiers in Marine Science, 2022)
Coral reefs are under stress throughout the world. To better understand the molecular mechanisms underlying coral biology and their genomic evolution, here we sequenced the genome and transcriptomes of elegance coral Catalaphyllia jardinei (Euphylliidae). This monotypic genus stony coral is widespread but rare, being found across the Indo-West Pacific, from the northern Indian Ocean, Australia, Philippines, to the South China Sea. Due to its popularity among aquarium hobbyists, it is an overexploited species collected in large quantities from the wild for aquarium trade. The assembled genome is ~ 651.3 Mb in total length and of high physical contiguity with a scaffold N50 size of 28.9 Mb. The gene copy numbers of abiotic stress regulator (heat shock protein family genes) and neuropeptides (GLWamide, GRFamide, PRGamide and HIRamide) are similar to other sequenced anthozoans, and we have also identified the first set of sesquiterpenoid biosynthetic pathway genes in coral. Sequencing of small RNAs allows us to identify 35 microRNAs in C. jardinei and update the number of conserved microRNAs in cnidarians. This study established a foundation for further investigation into the roles of sesquiterpenoids and microRNAs in development of coral and understand their responses to climate change. Due to the easiness to culture C. jardinei in reef tanks and the established resources in this study, we propose this species be adopted as a new laboratory model in environmental and ecological experiments aiming to understand coral biology and responses to environmental stressors.

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Targeting Ni-Cu mineralization in the Canadian High Arctic large igneous province: integrating geochemistry, magmatic architecture and structure - Benoit M. Saumur; Marie-Claude Williamson; Jean H. Bédard (Mineralium Deposita, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Supplementing selection decisions in a hybrid wheat breeding program by using F2 yield as a proxy of F1 performance - Anil Adhikari; Amir M. H. Ibrahim; Jackie C. Rudd; P. Stephen Baenziger; Amanda Easterly; Nick Garst; Vikas Belamkar; Jean-Benoit Sarazin (Euphytica, 2020)

Stress or injury induces cellular plasticity in salivary gland acinar cells - Andrew D. Shubin; Azmeer Sharipol; Timothy J. Felong; Pei-Lun Weng; Brittany E. Schutrum; Debria S. Joe; Marit H. Aure; Danielle S.W. Benoit; Catherine E. Ovitt (Cell and Tissue Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Genetic Mapping of Steroidal Glycoalkaloids Using Selective Genotyping in Potato - Jamuna Risal Paudel; Kyle M. Gardner; Benoit Bizimungu; David De Koeyer; Jun Song; Helen H. Tai (American Journal of Potato Research, 2019)

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Metabo-lipidomics of Fibroblasts and Mitochondrial-Endoplasmic Reticulum Extracts from ALS Patients Shows Alterations in Purine, Pyrimidine, Energetic, and Phospholipid Metabolisms - Charlotte Veyrat-Durebex; Céline Bris; Philippe Codron; Cinzia Bocca; Stéphanie Chupin; Philippe Corcia; Patrick Vourc’h; Rudolf Hergesheimer; Julien Cassereau; Benoit Funalot; Christian R Andres; Guy Lenaers; et al. (Molecular Neurobiology, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

Survival strategies of a frugivore, the sun bear, in a forest-oil palm landscape - Roshan Guharajan; Todd W. Arnold; Gilmoore Bolongon; Grace H. Dibden; Nicola K. Abram; Shu Woan Teoh; Mohd Azzumar Magguna; Benoit Goossens; Siew Te Wong; Senthilvel K. S. S. Nathan; David L. Garshelis (Biodiversity and Conservation, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Directional hydrostratigraphic units simulation using MCP algorithm - N. Benoit; D. Marcotte; A. Boucher; D. D’Or; A. Bajc; H. Rezaee (Stochastic Environmental Research and Risk Assessment, 2018)

Rapid Screening of Potato Cultivars Tolerant to Nitrogen Deficiency Using a Hydroponic System - Xiaofang Xie; Xiu-Qing Li; Bernie J. Zebarth; Suyan Niu; Ruimin Tang; Helen H. Tai; Benoit Bizimungu; Weiren Wu; Muhammad Haroon (American Journal of Potato Research, 2018)

Virus-induced gene silencing in Rauwolfia species - Cyrielle Corbin; Florent Lafontaine; Liuda Johana Sepúlveda; Ines Carqueijeiro; Martine Courtois; Arnaud Lanoue; Thomas Dugé de Bernonville; Sébastien Besseau; Gaëlle Glévarec; Nicolas Papon; Lucia Atehortúa; Nathalie Giglioli-Guivarc’h; et al. (Protoplasma, 2017)

Virus-induced gene silencing of the two squalene synthase isoforms of apple tree (Malus × domestica L.) negatively impacts phytosterol biosynthesis, plastid pigmentation and leaf growth - Sandra M. Navarro Gallón; Carolina Elejalde-Palmett; Dimitri Daudu; Franziska Liesecke; Frédéric Jullien; Nicolas Papon; Thomas Dugé de Bernonville; Vincent Courdavault; Arnaud Lanoue; Audrey Oudin; Gaëlle Glévarec; Olivier Pichon; et al. (Planta, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Influences of climate and historical land connectivity on ant beta diversity in East Asia - Patricia H. Wepfer; Benoit Guénard; Evan P. Economo (Journal of Biogeography, 2016)
Aim Biodiversity patterns reflect both ecological and evolutionary processes interacting with geographical variation in climate and the current and historical connectivity between land areas. We sought to disentangle these effects in explaining the organization of ant diversity across geographical areas and islands in East Asia. Location The Japanese Archipelago including the Ryukyu and Ogasawara Islands, Taiwan and coastal continental regions of Korea, China and Russia. Methods We aggregated species occurrence records from published literature, specimen databases and museum records, and compiled climatic variables for islands and politically defined continental areas. Current and historical land connections in the Last Glacial Maximum were determined using bathymetric databases. We analysed factors driving patterns of Simpson composition dissimilarity using multiple regression of distance matrices. Results Temperature was the largest driver of dissimilarity among areas, with geographical distance and historical land contiguity also being important. Current land contiguity had no detectable effect. Main conclusions We found climate to be a primary driver of ant diversity patterns on large scales, consistent with previous work on ants and other organisms. Interestingly, land connectivity during historical periods of low sea level was more important than current land connectivity in explaining faunal similarities. This implies that despite the potential overwater dispersal of ants, overland dispersal via transient land connections is a more important driver of regional‐scale biogeographical pattern in East Asia.

Lack of association between dopaminergic antagonism and negative symptoms in schizophrenia: a positron emission tomography dopamine D2/3 receptor occupancy study - Gagan Fervaha; Fernando Caravaggio; David C. Mamo; Benoit H. Mulsant; Bruce G. Pollock; Shinichiro Nakajima; Philip Gerretsen; Tarek K. Rajji; Wanna Mar; Yusuke Iwata; Eric Plitman; Jun Ku Chung; et al. (Psychopharmacology, 2016)

Toluene diisocyanate and methylene diphenyl diisocyanate: asthmatic response and cross-reactivity in a mouse model - Lore Pollaris; Fien Devos; Vanessa De Vooght; Sven Seys; Benoit Nemery; Peter H. M. Hoet; Jeroen A. J. Vanoirbeek (Archives of Toxicology, 2016)

B acillus subtilis attachment to A spergillus niger hyphae results in mutually altered metabolism - Isabelle Benoit; Marielle H. van den Esker; Aleksandrina Patyshakuliyeva; Derek J. Mattern; Felix Blei; Miaomiao Zhou; Jan Dijksterhuis; Axel A. Brakhage; Oscar P. Kuipers; Ronald P. de Vries; Ákos T. Kovács (Environmental Microbiology, 2015)
Summary Interaction between microbes affects the growth, metabolism and differentiation of members of the microbial community. While direct and indirect competition, like antagonism and nutrient consumption have a negative effect on the interacting members of the population, microbes have also evolved in nature not only to fight, but in some cases to adapt to or support each other, while increasing the fitness of the community. The presence of bacteria and fungi in soil results in various interactions including mutualism. Bacilli attach to the plant root and form complex communities in the rhizosphere. B acillus subtilis , when grown in the presence of A spergillus niger , interacts similarly with the fungus, by attaching and growing on the hyphae. Based on data obtained in a dual transcriptome experiment, we suggest that both fungi and bacteria alter their metabolism during this interaction. Interestingly, the transcription of genes related to the antifungal and putative antibacterial defence mechanism of B . subtilis and A . niger , respectively, are decreased upon attachment of bacteria to the mycelia. Analysis of the culture supernatant suggests that surfactin production by B . subtilis was reduced when the bacterium was co‐cultivated with the fungus. Our experiments provide new insights into the interaction between a bacterium and a fungus.

Pesticide risk assessment and management in a globally changing world—report from a European interdisciplinary workshop - Marc Babut; Gertie H. Arts; Anna Barra Caracciolo; Nadia Carluer; Nicolas Domange; Nikolai Friberg; Véronique Gouy; Merete Grung; Laurent Lagadic; Fabrice Martin-Laurent; Nicolas Mazzella; Stéphane Pesce; et al. (Environmental Science and Pollution Research, 2013)

Evolutionary history of almond tree domestication in the M editerranean basin - M. Delplancke; N. Alvarez; L. Benoit; A. Espíndola; H. I Joly; S. Neuenschwander; N. Arrigo (Molecular Ecology, 2013)
Genetic diversity of contemporary domesticated species is shaped by both natural and human‐driven processes. However, until now, little is known about how domestication has imprinted the variation of fruit tree species. In this study, we reconstruct the recent evolutionary history of the domesticated almond tree, Prunus dulcis , around the Mediterranean basin, using a combination of nuclear and chloroplast microsatellites [i.e. simple sequence repeat ( SSR s)] to investigate patterns of genetic diversity. Whereas conservative chloroplast SSR s show a widespread haplotype and rare locally distributed variants, nuclear SSR s show a pattern of isolation by distance with clines of diversity from the East to the West of the Mediterranean basin, while Bayesian genetic clustering reveals a substantial longitudinal genetic structure. Both kinds of markers thus support a single domestication event, in the eastern side of the Mediterranean basin. In addition, model‐based estimation of the timing of genetic divergence among those clusters is estimated sometime during the Holocene, a result that is compatible with human‐mediated dispersal of almond tree out of its centre of origin. Still, the detection of region‐specific alleles suggests that gene flow from relictual wild preglacial populations (in North Africa) or from wild counterparts (in the Near East) could account for a fraction of the diversity observed.

Extreme Conservation of the psaA/psaB Intercistronic Spacer Reveals a Translational Motif Coincident with the Evolution of Land Plants - Elena L. Peredo; Donald H. Les; Ursula M. King; Lori K. Benoit (Journal of Molecular Evolution, 2012)

Observations of Thin Layers in Coastal Hawaiian Waters - Margaret A. McManus; Jeff C. Sevadjian; Kelly J. Benoit-Bird; Olivia M. Cheriton; Amanda H. V. Timmerman; Chad M. Waluk (Estuaries and Coasts, 2012)

Molecular cloning and functional characterization of Catharanthus roseus hydroxymethylbutenyl 4-diphosphate synthase gene promoter from the methyl erythritol phosphate pathway - Olivia Ginis; Vincent Courdavault; Céline Melin; Arnaud Lanoue; Nathalie Giglioli-Guivarc’h; Benoit St-Pierre; Martine Courtois; Audrey Oudin (Molecular Biology Reports, 2012)

Defining the Turkey MHC: identification of expressed class I- and class IIB-like genes independent of the MHC-B - Kent M. Reed; Miranda M. Bauer; Melissa S. Monson; Benjamin Benoit; Lee D. Chaves; Thomas H. O’Hare; Mary E. Delany (Immunogenetics, 2011)

Increased cave dwelling reduces the ability of cave crickets to resist dehydration - Jay A. Yoder; Joshua B. Benoit; Michael J. LaCagnin; Horton H. Hobbs (Journal of Comparative Physiology B, 2011)

Balancing Risk and Costs to Optimize the Clinical Supply Chain—A Step Beyond Simulation - Chedia Abdelkafi; Benoît H. L. Beck; Benoit David; Cédric Druck; Mitchell Horoho (Journal of Pharmaceutical Innovation, 2009)

Proteins prenylated by type I protein geranylgeranyltransferase act positively on the jasmonate signalling pathway triggering the biosynthesis of monoterpene indole alkaloids in Catharanthus roseus - Vincent Courdavault; Vincent Burlat; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Cell Reports, 2009)

A high blood lactate induced by heavy exercise does not affect the increase in submaximal $$\dot V{\text{O}}_2 $$ with hyperoxia - F. B. Favier; F. Prieur; O. Grataloup; T. Busso; J. Castells; C. Denis; A. Geyssant; H. Benoit (European Journal of Applied Physiology, 2005)

CaaX-prenyltransferases are essential for expression of genes involvedin the early stages of monoterpenoid biosynthetic pathwayin Catharanthus roseus cells - Vincent Courdavault; Martine Thiersault; Martine Courtois; Pascal Gantet; Audrey Oudin; Pierre Doireau; Benoit St-Pierre; Nathalie Giglioli-Guivarc’h (Plant Molecular Biology, 2005)

Energy, transport and waste models - Jan Braam; Toini M. Tanner; Cecilia Askham; Nicoline Hendriks; Benoit Maurice; Helena Mälkki; Mie Vold; Helena Wessman; Angeline S. H. de Beaufort (The International Journal of Life Cycle Assessment, 2001)

Framework for modelling data uncertainty in life cycle inventories - Mark A. J. Huijbregts; Gregory Norris; Rolf Bretz; Andreas Ciroth; Benoit Maurice; Bo von Bahr; Bo Weidema; Angeline S. H. de Beaufort (The International Journal of Life Cycle Assessment, 2001)

A system to simulate gas exchange in humans to control quality of metabolic measurements - F. Prieur; T. Busso; J. Castells; R. Bonnefoy; H. Benoit; A. Geyssant; C. Denis (European Journal of Applied Physiology, 1998)

Lateral forces in AFM imaging and immobilization of cells and organelles - M. Benoit; T. Holstein; H. E. Gaub (European Biophysics Journal, 1997)

Accuracy of pulse oximetry during intense exercise under severe hypoxic conditions - H. Benoit; F. Costes; L. Feasson; J. R. Lacour; F. Roche; C. Denis; A. Geyssant; J. C. Barthlmy (European Journal of Applied Physiology, 1997)